Aminoglycocides as An Alternative Antibiotic Therapy Against Urinary Tract Infection in Children due to Extended-Spectrum Β-Lactamase (ESBL) Producing Escherichia Coli in Carbapenem Trends - Mapindra, Muhammad Pradhika; Mahindra, Muhammad Pradhiki; Ramadhan, Muhammad; Putri, Apriska Mega Sutowo (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Extended-spectrum β-lactamase (ESBL) is an enzyme produced by certain Escherichia coli and Klebsiella pneumoniae. ESBL can induce theantibiotic resistance for betalactam antibiotics such as penicillin, cephalosporin, etc. Frequent utilization of carbapenem may induce the risk for carbapenem resistant against ESBLs producing microorganisms. This stud aimed to communicate Aminoglycocides as an alternative antibiotic therapy against urinary tract infection in children.Case Presentation: We present a case of 4 years child who was admitted to the state hospital of Madiun with main complaint of 10 days high fever accompanied by phimosis appearance. Laboratory results based on urine culture show the ESBL positive Escherichia coli. Results: We have used aminoglycoside for treating the patient. Clinical presentation in this patient start showing an improved clinical response and negative bacteriuria in the second urine test after the aminoglycoside therapy.Conclusion: Aminoglycosides such as gentamicin can be considered to be one of the best options for treating an ESBL infection beside carbapenem in order to reduce the carbapenem trend In clinical setting of the urinary tract infection caused by ESBL Eschericia coli.Keywords: Aminoglycosides, Carbapenem, Extended-spectrum β-lactamase, Gentamicin, urinary tract infectionCorrespondence: Muhammad Pradhika Mapindra. General Practitioner in State Hospital of Madiun, Easy Java. Email: mpradhika57@gmail.com.Indonesian Journal of Medicine (2020), 05(03): 200-205https://doi.org/10.26911/theijmed.2020.05.03.04